2019
DOI: 10.1039/c9ra05728e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water evaporation/absorption on the stability of glycerol–water marbles

Abstract: The influence of water evaporation and absorption on the stability of aqueous glycerol marbles was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…The subscripts s and w represent the salt and water components, respectively. The experimental results indicated that the salt solution was completely precipitated in 1500 s; consequently, the mass of each component at each time was calculated such that the mass of the water component evaporated in 1500 s. Eqn (5) shows the formula to calculate the mass fraction used.…”
Section: Comparison With Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The subscripts s and w represent the salt and water components, respectively. The experimental results indicated that the salt solution was completely precipitated in 1500 s; consequently, the mass of each component at each time was calculated such that the mass of the water component evaporated in 1500 s. Eqn (5) shows the formula to calculate the mass fraction used.…”
Section: Comparison With Theorymentioning
confidence: 99%
“…The dynamics of evaporation for sessile droplets on a solid substrate have been extensively studied over the past decades. [1][2][3][4][5] While it is useful to investigate the evaporation behavior of sessile droplets, complex wetting dynamics by the interaction between the droplet and solid substrate should also be taken into account to understand the nature of the evaporation. Ideally, it is desirable to investigate the evaporation dynamics in mid-air without the wall effect.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of glycerol in water generally reduces water activity which in turn hinders droplet evaporation. With 50% glycerol in water, it was previously reported that the glycerol-water droplet will have minimal evaporation in an environment with RH = 0.66; hence, evaporation is neglected in the numerical simulations [ 37 ]. The simulated particles are also assumed to be noninteracting in this set of simulations due to the low particle concentration (<1 ppm).…”
Section: Methodsmentioning
confidence: 99%
“…[122] This does not occur in the ethanol-water LM as both experience vapor loss over time. [173] Balancing of evaporation and absorption in glycerol/water LMs could allow for long lasting lifetimes crucial for numerous applications, such as rapid gas evolution, with other studies showing that neither evaporation or deformation of pure glycerol LM occurred during heating at 90 °C over 8 h. [122,174] Additionally, coating particles that are pH responsive have been developed, the LMs formed therefore have extended or reduced lifetimes in different pH conditions with the same coating. Depending on the coating developed these LMs can be stable on an alkaline solution and collapse on an acidic solution or vice versa.…”
Section: Internal and External Environmentsmentioning
confidence: 99%
“…Monolayer and multilayered LMs have a ≈20% shorter and ≈30% longer lifetime than their equivalent naked droplets, respectively [24,138]. Relative humidity improves the lifetime of a multilayered LMs by up to ≈200% for a relative humidity of 80% [17,18,122]. The dramatic effect fully submerging the LM can have on lifetime, compared to the other factors, is also highlighted [19,20].…”
mentioning
confidence: 90%